2017
DOI: 10.2196/publichealth.7526
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Information Seeking on the Internet Among Sexual Minority People: Cross-Sectional Analysis From the Health Information National Trends Survey

Abstract: BackgroundIndividuals who face barriers to health care are more likely to access the Internet to seek health information. Pervasive stigma and heterosexism in the health care setting are barriers to health care for sexual minority people (SMP, ie, lesbian, gay, and bisexual people); therefore, SMP may be more likely to use the Internet as a source of health information compared to heterosexual people.ObjectiveCurrently, there is a dearth of published empirical evidence concerning health information seeking on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…As a group of individuals who face multiple barriers to contact with health professionals, sexual minorities are also more likely than heterosexual people to access the internet at higher rates than heterosexual people to seek health information. For example, one study found that sexual minority participants were 58% more likely to watch a health-related video on YouTube than heterosexual participants [ 59 ]. Yet, only a limited number of videos focused on other sexual minority populations at a high risk of contracting HIV, namely the transgender community.…”
Section: Discussionmentioning
confidence: 99%
“…As a group of individuals who face multiple barriers to contact with health professionals, sexual minorities are also more likely than heterosexual people to access the internet at higher rates than heterosexual people to seek health information. For example, one study found that sexual minority participants were 58% more likely to watch a health-related video on YouTube than heterosexual participants [ 59 ]. Yet, only a limited number of videos focused on other sexual minority populations at a high risk of contracting HIV, namely the transgender community.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence about whether LGB persons are more or less likely to use the Internet to seek out health information. 17,18 To our knowledge, no research exists about cancer-specific health information-seeking behaviors in LGB populations. Similarly, fatalistic cancer views have not been assessed specifically in healthy LGB populations or among LGB individuals diagnosed with cancer, and disparities in these fatalistic views have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of data from the Health Information National Trends Survey follow-up (2013-2017) have shown that, compared to heterosexuals, sexual minorities are more likely to view health videos on YouTube, have increased incidental exposure to health information online, and communicate with health care providers by email. 37,38 Sexual minorities were also more likely than heterosexual participants to report looking for information about health topics, but less likely to first seek health information from a physician. 38 These findings suggest that the patterns of health information seeking and engagement with HIT for sexual minorities may be different than for heterosexual individuals.…”
Section: Purposementioning
confidence: 99%